2020
DOI: 10.1093/eurjpc/zwaa084
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of particulate matter on cardiovascular morbidity in Italy: a national analysis

Abstract: Aims We aimed at investigating the relationship between particulate matter (PM) and daily admissions for cardiovascular diseases (CVDs) at national level in Italy. Methods and results Daily numbers of cardiovascular hospitalizations were collected for all 8084 municipalities of Italy, in the period 2013–2015. A satellite-based spatiotemporal model was used to estimate daily PM10 (inhalable particles) and PM2.5 (fine particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
3
25
2
Order By: Relevance
“…Estimates from different settings are important not only to have a more thorough and complete picture of the short-term effects of air pollution at population level across the entire geographical domain but also to improve the knowledge basis on low-level exposure effects. Recently, a U.S. study conducted on the Medicare population, a cohort of subjects aged 65 years and over enrolled in the U.S. health insurance system, showed a significant effect of PM 2.5 on mortality also for exposure levels below the U.S. standard (35 μg/m 3 ) [ 20 , 21 ] In Europe, similar results were provided by an Italian study conducted at national level, which showed a positive association between PM 2.5 and cardiovascular hospitalizations for low concentrations [ 18 ]. Currently, the European Air Quality legislation has fixed the limit of daily concentration of PM 2.5 to 15 μg/m 3 and for PM 10 to 45 μg/m 3 , assuming there are no health effects below these levels.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Estimates from different settings are important not only to have a more thorough and complete picture of the short-term effects of air pollution at population level across the entire geographical domain but also to improve the knowledge basis on low-level exposure effects. Recently, a U.S. study conducted on the Medicare population, a cohort of subjects aged 65 years and over enrolled in the U.S. health insurance system, showed a significant effect of PM 2.5 on mortality also for exposure levels below the U.S. standard (35 μg/m 3 ) [ 20 , 21 ] In Europe, similar results were provided by an Italian study conducted at national level, which showed a positive association between PM 2.5 and cardiovascular hospitalizations for low concentrations [ 18 ]. Currently, the European Air Quality legislation has fixed the limit of daily concentration of PM 2.5 to 15 μg/m 3 and for PM 10 to 45 μg/m 3 , assuming there are no health effects below these levels.…”
Section: Introductionmentioning
confidence: 70%
“…Only few studies have focused on the different effects in these settings. Recently, Italian rural areas were considered in a study on the short-term exposure to PM on cardiovascular hospital admissions [ 18 ]. The authors assessed the associations both in urban and rural areas to test potential different effects.…”
Section: Introductionmentioning
confidence: 99%
“…The average PM 2.5 and ozone concentrations across Quebec are lower than the standard air pollutant levels of 8.8 µg/m 3 and 62 ppb (for 8-h average) respectively defined by the Canadian Ambient Air Quality Standards (CAAQS) [ 22 ]. In fact, health effects below the CAAQS standards have been demonstrated in many previous studies [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 89%
“…Some epidemiology studies show that acute, short‐term of PM 2.5 exposure is associated with increased CVD hospitalisation (Qiu et al., 2020 ), especially for heart failure admissions (Stafoggia et al., 2020 ). Cardiac troponin T assessment demonstrates that acute PM exposure may elevate myocardial damage (Zhang et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inhibition of EVs secretion, downregulation of miR-421 content or activation of ACE2 can attenuate PM 2.5induced cardiomyocytes apoptosis and cardiac dysfunction, which would be potential therapeutical strategies for treating air pollution related CVD. Some epidemiology studies show that acute, short-term of PM 2.5 exposure is associated with increased CVD hospitalisation (Qiu et al, 2020), especially for heart failure admissions (Stafoggia et al, 2020). Cardiac troponin T assessment demonstrates that acute PM exposure may elevate myocardial damage (Zhang et al, 2021).…”
Section:  Discussionmentioning
confidence: 99%